Effects of Function-Based Academic and Behavior Intervention Plan in a Thai Inclusive School - ตันติเฉลิม ชนิศา (Ratchaphruek Journal, 2018)
ABSTRACT The academic and behavior intervention plan based on the Functional Behavior Assessment (FBA) technology has been among the student support approaches with the strongest international empirical research support. The research has well documented the impacts of function-based intervention in reducing problem behavior and increasing desired behavior for students at-risk for learning problems. In Thailand, to document such effects in schools has been complex due to numbers of impediments found at the practice level. More studies are required to investigate the extent to which the approach impacts students’ classroom behaviors as well as the school implementation. This study employs a combined single-subject design to study behaviors of third primary graders at-risk for learning problem outcomes in a model inclusive school under the Office of the Basic Education Commission. The study purposes are to study (a) the effects of the function-based academic and behavior intervention on problem behavior and desired behavior of the at-risk students, (b) the maintenance of the behavioral changes as a result of using the plan, and (c) how the team including the administrator, the general education teachers, the special education teachers, the parents, and the behavior consultant accept the use of the plan in the aspects of goals, procedures, and effects. The intervention plan was designed to include the FBA data, team-based decision-making, and multicomponent intervention strategies. The results indicate that (a) the intervention plans have a potential to reduce problem behaviors and increase desired behaviors for all students, (b) the behavioral changes are somewhat promising, and (c) the team members accepted the intervention plans at a high level. Implications for practices and future research are described. The findings about how the function-based academic and behavior intervention plan come to be a promising approach to promote more meaningful inclusive outcomes are discussed.